El Salvador : Report on the Observance of Standards and Codes (ROSC)-Data Module. (IMF Staff Country Reports; Country Report, 2004)
This Report on the Observance of Standards and Codes (ROSC) on the Data Module on El Salvador reviews summary assessment of data quality. Dissemination of data subject to the IMF's Special Data Dissemination Standard (SDDS) is in observance of all SDDS specifications, including data coverage, periodicity, timeliness, and the dissemination of advance data release calendars. IMF staff recommends provision of a sufficient budgetary, human resource, and information technology resource allocation to agencies to assure the production of essential source data and significant quality improvements in all areas of macroeconomic statistics.